THE EFFECT OF TOURISTS MOTIVATION AT BATU ANGUS NATIONAL PARK REVISIT INTENTION - Kezia Eunike Sumendap; James D. D. Massie; Merinda H. C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
In recent years, there has been a significant increase in the popularity of water-based tourism in Manado, particularly in the form of water sports and diving activities. Manado is known for its stunning marine biodiversity, including coral reefs, a variety of fish species, and other sea creatures. This has attracted a growing number of tourists, both domestic and international, seeking to explore the underwater world and enjoy the natural beauty of the area. This study aimed to explore the effect of tourists' motivation on their revisit intention to Batu Angus National Park, a popular tourist destination in Indonesia. Using a quantitative research approach, data was collected through a survey questionnaire distributed to tourists who had previously visited the park around 100 sample. The study findings indicated that the variable push motivation and pull motivation are significanlty influenced the variable revisit intention to the park. The study provides useful insights for park management and policymakers to enhance visitors' experience by catering to their motivational needs, which in turn can increase their revisit intention and boost tourism development in the region. Additionally, improving facilities such as adding more benches, rest areas, and public restrooms would provide greater convenience and comfort to visitors. These enhancements would not only attract more tourists to the park but also increase their revisit intention, which could potentially boost tourism development in the region.   Keywords: push motivation, pull motivation, revisit intention